Inheritance of pod shattering in soybean [Glycine max (L.) Merrill.]: INHERITANCE OF POD SHATTERING IN SOYBEAN - DILIP S THAKARE; VIVEK P CHIMOTE; M P DESHMUKH; R C ROKADE; A T ADSUL (Journal of Oilseeds Research, 2017)
In the present investigation, inheritance of pod shattering in soybean was studied in three crosses involving four parents, among them MACS-450 and DS-9712 were tolerant to pod shattering while Monetta and Kalitur were susceptible to pod shattering. The contrasting parents were used to develop three cross combinations viz., Monetta × MACS-450, Kalitur × DS-9712 and Kalitur × MACS-450. Inheritance of pod shattering was found to be governed by partial dominance of susceptibility over the resistance. Two major genes with inhibitory epistasis were involved in inheritance of pod shattering in soybean. As regardsto inheritance of pod shattering tolerance parents MACS-450 and DS-9712, F1s of susceptible × resistant crosses and backcrosses with resistant parent showed tolerance. Two major genes with inhibitory epistasis were involved in inheritance of pod shattering in soybean as evidenced from F2 ratio (13:3) and confirmed by test cross ratio (3:1) in tolerant × susceptible crosses. Two dominant genes with inhibitory epistasis were involved in the inheritance of pod shattering tolerance in soybean.